Freedom in the Face of Nicaragua's Hybrid Carceral System. Issue 1 (1st March 2020) - Weegels, Julienne
Abstract: Drawing on extensive prisons research and sustained contact with (former) prisoners in Nicaragua, this article explores three former prisoners' post-release trajectories. In the face of a hybrid state that manifests as both a legal penal state and an extralegal system of powers, colloquially referred to as el Sistema (the System), and to the backdrop of a (d)evolving political context, I argue for an understanding of the 'tightness' of post-release life by conceptualizing the Sistema's transcarceral grip. Former prisoners deal with this grip in different ways, ranging from self-censorship to the taking of 'delinquent freedoms'. A detailed understanding of this grip can help pinpoint how carceral logics are mobilized outside prison in Nicaragua and how its carceral state expands through not only legal but also extralegal means.